II–1 Compliance of Low-Intensity Pulsed Ultrasound (LIPUS) for Fresh Fractures. Issue 5 (May 2015) - Matsubara, Takamasa; Sano, Michio; Morioka, So; Aoki, Kentaro; Shimizu, Tomohiko; Ide, Koichiro; Nanba, Mitsuhiro; Hagiwara, Kazuhiro; Okabayashi, Ryo
Abstract : Introduction: The great majority of clinical data that have been reported are related to the effect of low-intensity pulsed ultrasound (LIPUS) on the healing of fresh fractures. Objective: The aim of this study was to investigate compliance with LIPUS treatment for fresh fractures. Methods: The subjects were 94 patients (average age at the time of surgery was 56.4 years) who were given the LIPUS after the surgical operation for fresh fractures conducted between 2008 and 2013. We have defined LIPUS compliance rate (Number of days during which LIPUS was actually used / Number of days during which LIPUS was rented × 100). We have evaluated that LIPUS execution rate after dividing into good group (LIPUS execution rate ≥ 80%) and poor group (<80%). Age, Number of days during which LIPUS was rented, and fracture site were compared in the 2 groups. To determine differences between the 2 groups, we performed Student t test for age and Number of days during which LIPUS was rented. Chi-square tests were used to determine associations with fracture site between the 2 groups. Results: Average LIPUS compliance rate was 79% (6.6–100%). Average number of days during which LIPUS was rented was 145.2 days (22–370 days). The bone union rate was 97.8%. The average age was significantly higher in the poor group (60.8 years) than in the good group (50.6 years) ( P < 0.05). There was a statistically significant difference on the Number of days during which LIPUS was rented ( P < 0.01) between the good group (119.2 days) and poor group (164.5 days). There was a significant correlation between the LIPUS compliance rate and fracture site ( P < 0.01). And, there were more radius and tibia for the good group and more femur and humerus for the poor group. Conclusions: The present study suggests that compliance of LIPUS for fresh fractures was influenced by age, number of days rented the LIPUS, fracture site.